The Relationship Between Adolescents Reproductive Health Knowledge and Personal Hygiene Attitudes and The Risk Of Sexually Transmitted Infections (STIs) in Kedung Jaya Village, Babelan, in 2025 - Putri Ridhotun Nabila; Indah Yuliani (Jurnal Ners, 2026)
Sexually Transmitted Infections (STIs) are a reproductive health problem that remains prevalent among adolescents and is influenced by various factors, including reproductive health knowledge and personal hygiene practices. According to data from the Babelan Community Health Center (Puskesmas) (2023), approximately 20% of the 15,000 reproductive-age population in Kedung Jaya Village, Babelan District, Bekasi City, reported mild STI symptoms. Therefore, this research is expected to provide a basis for developing reproductive health education programs and fostering personal hygiene behaviors for adolescents as an STI prevention effort. This study employed a cross-sectional method, a research design that involves observations or measurements of both variables at the same time. In this study, the relationship between variables was analyzed using the Chi-Square test to determine whether there is a significant relationship between the independent and dependent variables.Based on the Chi-Square test, the Asymp. Sig. (p-value) was 0.000 (p < 0.05), indicating a significant relationship between personal hygiene attitudes in adolescents and the risk of sexually transmitted infections (STIs). Therefore, personal hygiene attitudes are an important factor in reducing the risk of STIs in adolescents.The results of the relationship analysis indicate a tendency that low levels of reproductive health knowledge are followed by a higher risk of sexually transmitted infections (STIs). Most respondents were in mid-adolescence, specifically between the ages of 14 and 16, which is a critical phase in the formation of knowledge, attitudes, and behaviors related to reproductive health. It is hoped that there will be increased reproductive health education and fostering personal hygiene attitudes among adolescents as an effort to prevent sexually transmitted infections (STIs).